Nasilenie wymiarów konstytuujących postawę wobec edukacji a percepcja źródeł własnej skuteczności u osób odbywających karę pozbawienia wolności - Maziarczyk, Piotr; Mikołajczak, Mateusz; Kalinowski, Mirosław; Niewiadomska, Iwona; Jurek, Krzysztof (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2024)
Education in prisons is a significant aspect of prisoner rehabilitation and resocialization, yet it is often marginalized in public discourse and penitentiary policy. This study examines the challenges and prospects of education within the prison system, focusing on the needs of prisoners and the resources and opportunities available to them. The research aims to investigate the relationship between the intensity of various aspects of attitudes towards education among prisoners and their perception of self-efficacy. The study was conducted on 115 individuals serving sentences in penitentiary units within the Lublin District of the Polish Prison Service. Empirical analyses revealed significant correlations between the emotional attitudes towards education and the perception of personal successes and failures, the level of experienced stress, and persuasion from others. Meanwhile, the intensity of the cognitive attitudes towards education significantly correlated with the perception of persuasion from others, while the intensity of the behavioural aspects correlated with the level of experienced stress. Prisoners may simultaneously exhibit conflicting beliefs about education, which can be both positive and negative while experiencing high levels of stress, which indicates a loss of resources, and being successful, which reflects on capital gains.